ENGLISH FOR TOURISM LECTURES BECOME MORE CREATIVE WITH MODIFIED CONCEPTS OF CTL (CONTEXTUAL TEACHING AND LEARNING) - Vera Kristiana; Ayu Melati Ningsih (PROJECT (Professional Journal of English Education), 2020)
This research examined the modification of the concept of CTL (Contextual Teaching and Learning) in English for Tourism lectures in English literature studies at the Muslim Nusantara Al-Washliyah University, Medan. English For Tourism lectures involved theoretical and practical training in their implementation. One important theory taught to students was about how to communicate well and correctly in the world of tourism. Students often experienced difficulties in communicating and understanding various very diverse cultures in Indonesia in particular and in foreign countries in general. Language and culture learning not only provided an understanding of the definition but students were required to be able to find their own knowledge. Lecturers must have concepts that spur students to be able to think critically and creatively. One of the appropriate learning concepts for teaching English for Tourism courses was the concept of CTL (Contextual Teaching And Learning). The concept made it easier for students to understand all the theories that were conveyed during the lecture. CTL made innovative, creative and effective learning. CTL modification in English for Tourism lectures could make lectures more creative, and require students to think more critically. This meant they were encouraged to connect between the materials taught with everyday life in the world of tourism. Keywords:  Modification, CTL, English for Tourism